2021
DOI: 10.1186/s12967-021-02761-1
|View full text |Cite
|
Sign up to set email alerts
|

High lymphocyte population-related predictive factors for a long-term response in non-small cell lung cancer patients treated with pemetrexed: a retrospective observational study

Abstract: Background Regimens combining pemetrexed (PEM) and immune checkpoint inhibitors (ICIs) targeting programmed cell death-1 (PD-1) or programmed death-ligand 1 (PD-L1) are widely used for the treatment of advanced non-squamous non-small-cell lung cancer (NSq-NSCLC). Recently, PEM was shown to induce immunogenic cell death (ICD) and to enhance immune-regulatory genes. Some patients demonstrate an extremely long-term response to PEM. It is possible that the continued response in these patients is de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“… 84 While diminution of the ANC during treatment is associated with a better patient response to ICI in lung cancer, 85 86 high baseline ALC associates with better response to ICI in HNC 87 and patients with NSCLC. 88 Hence, the NLR prognostic value comes from the cointegration of the ANC and ALC, which it is determined by biogenesis as well as survival of both neutrophils and lymphocytes ( figure 3 ).…”
Section: Nlr As a Marker Of The Response To Icismentioning
confidence: 99%
“… 84 While diminution of the ANC during treatment is associated with a better patient response to ICI in lung cancer, 85 86 high baseline ALC associates with better response to ICI in HNC 87 and patients with NSCLC. 88 Hence, the NLR prognostic value comes from the cointegration of the ANC and ALC, which it is determined by biogenesis as well as survival of both neutrophils and lymphocytes ( figure 3 ).…”
Section: Nlr As a Marker Of The Response To Icismentioning
confidence: 99%
“…For example, chromomycin A5 (CA5) can serve as a bona fide ICD inducer, since it enhances the activation of APCs and T-cells in syngeneic mouse models vaccinated with metastatic melanoma B16-F10 cells ( Florêncio et al, 2022 ). Additionally, pemetrexed is a multi-targeting antifolate antagonist established as the first-line chemotherapeutic drug for advanced lung adenocarcinoma, and mesothelioma which increases immune-regulatory genes and induces ICD ( Mathew et al, 2018 ; Sumiyoshi et al, 2021 ).…”
Section: Icd Inducers and Molecular Mechanismmentioning
confidence: 99%
“…But the research by Fileswasser et al has shown that oxaliplatin does not induce ICD in NSCLC cells (4). Pemetrexed, a multi-targeting antifolate antagonist which is established as the main chemotherapy drug for the first-line treatment of advanced non-squamous NSCLC (NSq-NSCLC) and mesothelioma, has also been shown to induce ICD and to increase of immune-regulatory genes (177,178). Liu et al found that crizotinib, a kind of drugs used to treat NSCLC patients which carries activated ALK/ROS1, is an efficient ICD stimulator via off-target effects (162).…”
Section: Chemotherapy and Radiation Therapymentioning
confidence: 99%
“…The antitumor effect of ICIs works by interfering with immune tolerance (178). The most clinically common immune checkpoints include: PD-1/PD-L1, cytotoxic T lymphocyteassociated antigen-4 (CTLA-4), indoleamine 2.3-dioxygenase (IDO), and CD47 (197,198).…”
Section: Icismentioning
confidence: 99%
See 1 more Smart Citation